Egyetemjáró zalai nemesek és a reformáció kezdetei a 16. századi Zalában - Bilkei, Irén (Gerundium, 2017)
Academical Noble Students from Zala County and the Beginning of the Reformation in Zala County in the 16th Century. The appearance and spread of the Reformation in Zala county in the 16th century has been hardly examined so far. It can be explained both by the low number of the sources and their low exploration. The new researches in connection with the 500th anniversary of the appearance of the Reformation have revealed several new, unexplored primary sources unknown up to the present and the publications on the Hungarian academica peregrinatio uncovered the academical home students of the mainly German, Protestant universities. Furthermore, the charters of the Zalavár and Kapornak convents as places of authentication (locus credibilis) and the notes of the minutes of the general meetings of Zala county can also be involved in the research. These diverse sources complete the well-known data of the Bánffy diary, the Canonica Visitatio of the Veszprém bishopric in 1554 and the personal letters of Tamás Nádasdy. However, it has to be mentioned that these sources contain only few direct details referring to the Reformation. Meanwhile, the noblemen residing in Zala county or having connection with it (Alsólendvai Bánffy, Nádasdy, Zrínyi) and their familiaris (Csányi, Háshágyi, Terjék, Zele, Kávásy and other families), who were devoted to the new religion or sympathized with it, and among them the students of Wittenberg, appear in several charters or minutes which demonstrate the obvious appearance, spread and social background of the Reformation in Zala county.